Species‐specific root proliferation of tree seedlings in tropical litter: do nutrients matter?. Issue 4 (22nd January 2020) - Sarker, Tushar C.; Maisto, Giulia; De Marco, Anna; Memoli, Valeria; Panico, Speranza C.; Motti, Riccardo; Idbella, Mohamed; Incerti, Guido; Mazzoleni, Stefano; Bonanomi, Giuliano
Abstract : Litter decomposition mobilizes nutrients that sustain ecosystem productivity, but decomposition by‐products may also hamper root proliferation by phytotoxicity. The aim of this study was to assess the litter substrate preferences of tropical tree seedlings in relation to litter chemical traits. We characterized 44 litter types (11 species at four decomposition ages; 0, 30, 90 and 180 days) for nutrients (N, P, K, Mg, Mn, Na, Fe and Zn) and proximate chemical parameters (cellulose, extractive, lignin and C) and tested the effect of such litter materials on seedling root growth of Albizia procera, Dalbergia sissoo and Terminalia arjuna . Albizia procera root growth was inhibited by all litter types and ages, including conspecific materials, while different heterospecific litters had inhibitory or stimulatory effect on D. sissoo and T. arjuna root growth, compared to the control. Interestingly, inhibitory and stimulatory effects of heterospecific litters significantly changed with litter age, although with no clear‐cut pattern among target species and litter species and age, while conspecific litters consistently inhibited root growth when aged, but not when fresh. Litter nutrient, extractive, C, cellulose and lignin showed no consistent association with root growth of tested plants. Albizia procera root growth was positively associated with Na content and N:P ratio. Dalbergia sissoo root growth was positively associated to C:N and lignin:N ratios, and negatively to K, Na and Zn content. Finally, T. arjuna root was positively associated to cellulose and N:P ratio, but negatively to extractive. We conclude that studied nutrient, cellulose and lignin do not consistently explain the species‐specific response of root of tree seedlings to decomposing litter.